Comprehensive analysis of the microstructure, properties and environmental performance of Al2O3-ZrO2 composites obtained via centrifugal slip casting. (14th December 2022) - Zygmuntowicz, Justyna; Tomaszewska, Justyna; Jeleń, Jakub; Piotrkiewicz, Paulina; Wachowski, Marcin; Torzewski, Janusz; Żurowski, Radosław
Graphical abstract: Highlights: Centrifugal slip casting as a method to form the finished casting in the form of ZTA. Examination of the relationship between Al2 O3 and ZrO2 in ZTA composites prepared by the CSC method. Influence of solid-phase contents on microstructure, phase composition, and mechanical properties. Abstract: This research investigates the possibility of preparing Al2 O3 -ZrO2 composites with different proportions of the Al2 O3 and ZrO2 phases by centrifugal slip casting (CSC) method and the effect of the solid phase content (50 vol%, 45 vol%, 40 vol%) on the microstructure and selected properties of the produced materials. The hardness results showed that all the series produced were characterised by high hardness, in the range of 16–19 GPa. The results of the static compression test demonstrated that increasing the solid phase content of the slip in the samples promotes the formation of fewer cracks during the monotonic compression loading of the composites. The LCA results demonstrated that as the content of ZrO2 in the composites increase, their environmental footprint increases.